2018
DOI: 10.15605/jafes.033.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Behaviors and Beliefs of Urban Adult Filipinos on Sunlight Exposure: A Qualitative Study

Abstract: Objective. To explore the attitudes, behaviors, and beliefs of urban adult Filipinos on sunlight exposure as an initial step in the development and validation of a culturally-appropriate questionnaire.Methodology. Focus groups were conducted among urban Filipinos 19 years old and above (n=38). The transcribed results underwent qualitative content and thematic analyses and were used to develop a conceptual framework.Results. Qualitative analysis revealed four main themes of sunlight exposure: internal influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Although the questionnaires served as important references, no questions were directly taken from any of these instruments, as they were all developed in countries of a different ethnicity, geography, and climate compared to the Philippines. Hence, we utilized a separate conceptual framework that explored additional aspects of sunlight exposure in Filipinos that may not have been covered in the existing questionnaires [11]. A unique feature of our questionnaire is the inclusion of questions pertaining to the perceived risks and benefits of sunlight exposure, which are significant determinants of an individual’s sunlight exposure practices.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their relevance (mainly the inclusion of different sun exposure variables and/or correlation with serum 25-OHD), the SEQs developed by Cargill et al [9] in Australia, Hanwell et al [8] in Italy, Humayun et al [6] in Pakistan, and Wu et al [7] in Hong Kong were used as references for this study. In addition, an existing conceptual framework on the attitudes, behaviors, and beliefs of urban adult Filipinos on sunlight exposure was also used (Figure 1) [11].…”
Section: Methodsmentioning
confidence: 99%
“…9 BCCs typically have a 15-20 years delay between the time of UV damage to clinical onset. 10 Yu et al 11 surveyed a sample of urban adult Filipinos and reported that different factors lead to perceived risks and benefits regarding sunlight exposure. Indoor occupations and hobbies negatively impacted sunlight exposure, while public transport positively impacted it.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In general, the subjects were aware of the dermatological risks of sun exposure and of common sun protection practices. 11…”
Section: Risk Factorsmentioning
confidence: 99%